Factors inhibiting the indigenous growth of the fertilizer industry in developing countries: report of the Ad Hoc Group of Experts from Fertilizer-Deficit Countries - United Nations (New York, United Nations, 1969)
This publication consists of two parts: part 1, the Group's report and recommendations; Part 2, the working papers presented at the meeting.
"United Nations publication. Sales no.: E. 69. II. B. 21."
Includes bibliographical references.
osc 29/01/2019
Loans
Keywords: Fertilizer industry